Robotic Process Automation in IT Services - Kruskopf, Mia (My University, 2019)
IT Service providers are facing growing pressure in delivering their services while meeting the client demands in time, quality and budget. Robotic Process Automation can help with these pressures. Robotic Process Automation, RPA, is a software tool that replicates human activities using the same user interfaces as humans use, without accessing the logical layers of business application. Gartner (2017) predicts that automation will change the way managed workplace services and service desk services are delivered and re-designing these services. RPA enables faster and more efficient execution of daily manual and repetitive tasks with lower costs (Willcocks et al. 2015) The purpose of this research was to examine how RPA is deployed, what benefits can be achieved with RPA and how are the benefits measured, and what challenges are related to RPA deployment. These were examined with systematic literature review and empirical research. The empirical research was conducted using grounded theory methodology and data was collected with semi-structured interviews. Findings of the empirical research suggest the following stages of RPA deployment: client engagement, process identification and automation tool selection, pre-development – that includes producing detailed description of the process, solution design and receiving appropriate permissions and accounts as well as appropriate test data – development and testing, releasing the robot into production as well as managing and maintaining the robots. Most common benefits were savings in cost and time, benefits for workforce like increase in employee productivity and satisfaction as well as process related benefits. Measurement is essential to prove the benefits of RPA to the management, and comparison between performance before and after robot in needed. The challenges in deployment were related to people related and the technology. The former included challenges in communication, engagement, process description accuracy as well as permissions and accounts. The latter were related to constraints of the technology.
Keywords: Processes, robotic process automation, automation, virtual workers